How Micro-Influencers, Brand Ambassadors, and Brand Communities Drive E-Commerce Sales - Octavianus, Vincent; Wijaya, Helidorus Fourtiando; Lestari, Shellda (APPS Publications, 2024)
This study tries to measure the influence of micro influencers, brand ambassadors and brand communities on luxury brand sales in e-commerce. To analyze the influence and relationships between the variables and potentially generalize findings, a quantitative research design is the method that involves collecting numerical data and using statistical analysis to identify patterns and test hypotheses. A survey method using questionnaires is a strong possibility for collecting data from a large enough sample of consumers who purchase luxury brands on e-commerce platforms. The study employs purposive sampling to target individuals who meet specific criteria, such as those who follow micro-influencers and brand ambassadors, are part of brand communities related to luxury brands, and have made luxury brand purchases on e-commerce platforms. This research found that micro-influencers, brand ambassadors, and brand communities each positively and significantly influence luxury brand purchasing behavior in e-commerce. Furthermore, the combined use of these three marketing strategies has a substantial positive impact on driving luxury brand sales online. While individual roles of micro-influencers, brand ambassadors, and brand communities might have been studied separately, this research provides empirical evidence for their combined and complementary influence on luxury brand purchasing behavior specifically within the e-commerce context.